Immune Responses to a Recombinant Glycoprotein E Herpes Zoster Vaccine in Adults Aged 50 Years or Older - Cunningham, Anthony L; Heineman, Thomas C; Lal, Himal; Godeaux, Olivier; Chlibek, Roman; Hwang, Shinn-Jang; McElhaney, Janet E; Vesikari, Timo; Andrews, Charles; Choi, Won Suk; Esen, Meral; Ikematsu, Hideyuki; et al. (The Journal of infectious diseases, 2018)
BACKGROUND: The herpes zoster subunit vaccine (HZ/su), consisting of varicella-zoster virus glycoprotein E (gE) and AS01B Adjuvant System, was highly efficacious in preventing herpes zoster in the ZOE-50 and ZOE-70 trials. We present immunogenicity results from those trials. METHODS: Participants (ZOE-50: ≥50; ZOE-70: ≥70 years of age) received 2 doses of HZ/su or placebo, 2 months apart. Serum anti-gE antibodies and CD4 T cells expressing ≥2 of 4 activation markers assessed (CD42+) after stimulation with gE-peptides were measured in subcohorts for humoral (n = 3293) and cell-mediated (n = 466) immunogenicity. RESULTS: After vaccination, 97.8% of HZ/su and 2.0% of placebo recipients showed a humoral response. Geometric mean anti-gE antibody concentrations increased 39.1-fold and 8.3-fold over baseline in HZ/su recipients at 1 and 36 months post-dose 2, respectively. A gE-specific CD42+ T-cell response was shown in 93.3% of HZ/su and 0% of placebo recipients. Median CD42+ T-cell frequencies increased 24.6-fold (1 month) and 7.9-fold (36 months) over baseline in HZ/su recipients and remained ≥5.6-fold above baseline in all age groups at 36 months. The proportion of CD4 T cells expressing all 4 activation markers increased over time in all age groups. CONCLUSIONS: Most HZ/su recipients developed robust immune responses persisting for 3 years following vaccination. CLINICAL TRIALS REGISTRATION: NCT01165177; NCT01165229.
Keywords: Immunity, Humoral; Female; herpes zoster; Viral Envelope Proteins; Lipid A; ženské pohlaví; Adjuvants, Immunologic; vakcinace; Herpes Zoster Vaccine; lidé; virus varicella zoster; Herpes Zoster; buněčná imunita; Herpesvirus 3, Human; vakcína proti pásovému oparu; protilátky virové; Humans; Vaccination; proteiny virového obalu; humorální imunita; Male; Aged; Vaccines, Subunit; lipid A; Immunogenicity, Vaccine; subjednotkové vakcíny; Immunity, Cellular; lidé středního věku; CD4-Positive T-Lymphocytes; senioři; mužské pohlaví; Antibodies, Viral; Saponins; imunogenicita vakcíny; adjuvancia imunologická; Middle Aged; saponiny; CD4-pozitivní T-lymfocyty